Effect of Dolomite Addition on The Performance of Palm Oil Mill Fly Ash for Methylene Blue Adsorption - Elda Pelita; Rita Youfa; Desniorita; Anang Baharuddin Sahaq; Miftahurrahmah; Resi Levi Permadani; Jerry (Indonesian Journal of Chemical Analysis (IJCA), 2023)
The use of palm oil mill fly ash (FA) as a low-cost adsorbent is one of the solutions for handling FA waste. In this study, the addition of dolomite is expected to improve the adsorbent performance. The aim of this study was to investigate the optimum FA-dolomite adsorbent composition and operating conditions for methylene blue adsorption. Different parameters were studied to optimize adsorption process such as the amount of dolomite, methylene blue flow rate, bed height and number of trays. FA-dolomite was converted into nano-adsorbent by sol-gel method which was coated on zeolite surface. Nano-adsorbents were characterized by XRF, FTIR, XRD and SEM. The adsorption capacity was tested by Spectrophotometer UV-Vis. XRF characterization showed that FA had the highest SiO2 content of 58.15%, while dolomite contained CaO of 52.72%. FTIR characterization detected the groups of Si-O-Si, Si-O-Al, Ca-O and Si-O. XRD characterization showed the average crystalline size of FA-dolomite 2% adsorbent was 28.56 nm and SEM characterization showed fine pores on the adsorbent surface. The highest adsorption efficiency obtained at FA-dolomite 2% was 97.364% and the lowest obtained at FA-dolomite 8% was 13.16% with a flow rate of 500 ml/h, adsorbent height of 9 cm and 3 trays. The greater the amount of dolomite added, the absorption efficiency decreases.